Mycorrhizal fungi determine salt-marsh plant zonation depending on nutrient supply - Daleo, Pedro (2008)
1. Arbuscular mycorrhizal fungi (AMF) can affect nutrient uptake of associated plants and can v ary in function from mutualism to parasitism as nutrient availability increases; thus they may interact with nutrient availability to influence plant community structure. 2. We e xperimentally investigated the hypotheses that AMF can affect the community structure of salt marshes by affecting plant competitive ability. We focused on: Spartina densiflora , that domi- nates physically benign high marsh habitats and S. alterniflora , which dominates more stressful low marsh habitats. 3. Colonization by AMF increased S. densiflora growth at low nutrient levels, but reduced growth at high nutrient levels. Spartina alterniflora w as not colonized by AMF and showed increased growth only with nutrient amendment. Nutrient or fungicide additions resulted in S. alterniflora migrating to higher marsh elevations, displacing S. densiflora . When nutrient and fungicide addi- tions were made together, however, dominance of S. densiflora w as maintained in the high marsh. 4. Synthesis. These results show that AMF can affect the competitive ability of plants and can have a large impact on plant community structure. The community impacts of these symbioses may be especially sensitive to human-induced eutrophication, given that nutrient supply can modulate w hether AMF positively or negatively affect associated plants.